GAMBARAN EFIKASI DIRI IBU DALAM PEMBERIAN MAKAN ANAK BALITA - Solikhah, Maula Mar'atus; Rohmatika, Dheny (Journal of Advanced Nursing and Health Sciences, 2021)
Mother's self-efficacy in feeding toddlers is the mother's belief in feeding toddlers. The purpose of the study was to determine the description of the mother's self-efficacy in feeding children under five. The study used a survey descriptive design. A total of 47 parents of toddlers were asked to fill out a self-efficacy questionnaire in feeding and at the same time weighing their toddlers. The results of this study show a picture of self-efficacy, namely the respondents are almost the same in the category of good self-efficacy (51.1%) and low self-efficacy (48.9%). Recommendations need to be given an action to the group of mothers who have low self-efficacy.